(untitled) (Journal of actual problems of jurisprudence, 2024)
The article provides a criminological analysis of industrial injuries during mining and construction work in Kazakhstan for five years (from 2018 to 2022). Using methods of analysing absolute and relative statistical indicators of industrial accidents, as well as the method of extrapolation, the authors assess the current state and dynamics of accidents that caused death and injury to people and attempt to determine further trends in occupational injuries in the mining and construction sectors of the economy. Based on the research, they state that the picture of traumatism in the conduct of mining and construction works in the country is unfavourable. The total number of victims of mining operations has increased over five years, exceeding the figure in 2018 by 45.04 %. The injury rate during construction work increased to 1,393 or 116.30 %. The indicator of hidden injuries in the mining sector of the economy averages 15.2:1, and in the construction industry – 5.1:1, which is many times higher than the corresponding indicator of most developed countries in Europe and the United States. In this regard, the authors formulate proposals to improve the occupational safety system and minimise the consequences of accidents. Keywords: occupational safety, occupational safety, mining, construction work, occupational injury, injury prevention